(untitled)
A quadri-polar fuzzy (qP-F) set is an extension of a traditional fuzzy set that uses four degrees of membership to represent different aspects of belonging to provide a more detailed framework for handling uncertainty and vagueness. In this paper, we propose the notion of quadri-polar-(,ϑ)-fuzzy fantastic ideals (qP-(,ϑ)-FFI(s)) in BCI-algebras based on qP-F set. Also, the notion of quadri-polar-(_σ , _σ q_τ )-fuzzy fantastic ideals (qP-(_σ , _σ q_τ )-FFI(s)) is introduced, and the characterizations for an _σ -qP-F set and q_τ -qP-F set to be quadri-polar fuzzy ideals (qP-FI) in BCI-algebras are established. Furthermore, we present the qP-F TOPSIS technique for multi-criteria Group decision-making (MCGDM), which is a natural extension of the TOPSIS method and used to rank and choose the best alternatives under qP-F positive and negative ideal solutions. Finally, practical examples interpreting the applicability of our proposed qP-F-TOPSIS are solved. , number=4, journal=European Journal of Pure and Applied Mathematics, year=2024, month=Oct., pages=3129–3155